PERLINDUNGAN HUKUM BAGI PENGGUGAT YANG MENGALAMI KERUGIAN AKIBAT ITIKAD TIDAK BAIK TERGUGAT MELALUI GUGATAN WANPRESTASI PERALIHAN HAK MILIK ATAS JAMINAN HAK KEPEMILIKAN SEBIDANG TANAH BERDASARKAN PUTUSAN NOMOR :72/PDT.G/2021/PN.TJK - hendra wijaya (Fakultas Hukum Universitas Muhammadiyah Palu, 2023)
Default in the legal process itself is an act that is negligent in fulfilling its achievements and requires the party affected by the default to pay for the decision that will be decided by the judge later. The problem in this research is the legal protection for the Plaintiff, the Judge's consideration and the legal consequences of the Judge's decision as a form of legal protection for the Plaintiff who suffered losses due to the defendant's bad faith. The research method is normative and empirical juridical. Based on the research and legal protection for the Plaintiffs, it is to ask the Panel of Judges for legal certainty to punish the Defendants to vacate the object of the dispute a quo and state that the Defendants are no longer entitled to the object of dispute under the law as a result of the breach of promise or default by Defendant I and Defendant II. (Defendants) against the Plaintiff through a breach of contract in court in accordance with the provisions of the civil procedural law. The judge's consideration is to see that the case is a breach of contract which has caused harm to the Plaintiff as well as legal considerations based on evidence of action and authentic and supported by legal facts that were not revealed at trial.